2022
DOI: 10.1007/s13205-022-03225-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic potential clustered miRNAs in bladder cancer

Abstract: At specific genomic loci, miRNAs are in clusters and their association with copy number variations (CNVs) may exhibit abnormal expression in several cancers. Hence, the current study aims to understand the expression of miRNA clusters residing within CNVs and the regulation of their target genes in bladder cancer. To achieve this, we used extensive bioinformatics resources and performed an integrated analysis of recurrent CNVs, clustered miRNA expression, gene expression, and drug–gene interaction datasets. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
1
7
0
1
Order By: Relevance
“…Moreover, the DNA methylation status at the CpG site region approximately 17.6 kb upstream was reported to be critical in C19MC regulation (Tsai et al 2009 ). In our previous study (Ware et al 2022b ), we found that C19MC was upregulated and co-localized with RCNV in BCa. Further investigation revealed that C19MC member expression was not statistically significant in patient survival analyses.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the DNA methylation status at the CpG site region approximately 17.6 kb upstream was reported to be critical in C19MC regulation (Tsai et al 2009 ). In our previous study (Ware et al 2022b ), we found that C19MC was upregulated and co-localized with RCNV in BCa. Further investigation revealed that C19MC member expression was not statistically significant in patient survival analyses.…”
Section: Discussionmentioning
confidence: 59%
“…It is also noteworthy that most studies classified BC patients based on the expression level of the analyzed miRNAs, which is useful when addressing their implications. The most reported miRNAs in the different studies were miR-141 and -200, which were both members of the miR200 family in seven studies [39,41,51,62,63,65,68]; and according to the results, a high expression of these molecules was correlated with higher overall survival [39,51,62,65,68] and lower MIBC incidence [63]. Interestingly, these studies were performed on tumor tissue samples, while the only study using liquid biopsies showed that increased urine miR-200a levels were correlated with high-risk BC [41]; this could be explained by methodological variability amongst the studies.…”
Section: Mirnas As Prognostic Tools In Bcmentioning
confidence: 99%
“…Lastly, the members of the miR200 family (miR-200a, -200b, -200c, -141, and -429) were the most analyzed in the reviewed studies [39,41,51,62,63,65,68]. These miRNAs have been described as tumor suppressors in some cancers.…”
Section: Biological Plausibility Of Described Mirnas In Bcmentioning
confidence: 99%
“…It is well documented that miRNAs are involved in the regulation of all biological processes [51,52] , and a large body of research has demonstrated that the deregulation of miRNA expression is associated with the initiation, development, and metastatic dissemination of human tumor cells [53][54][55][56][57][58] . Recent studies have also shown that miRNA profiles of tumor cells can provide both diagnostic and prognostic information on tumor progression [59][60][61][62] . Importantly, tumor cells can exchange miRNAs with both neighboring and distant cells via EVs.…”
Section: Introductionmentioning
confidence: 99%